The 1971 Indo-Pak War : A Soldier's Narrative - Qureshi, Hakeem Arshad Maj. Gen. (Karachi Oxford University Press, 2007)
"The 1971 India-Pakistan war involved civil insurgency, cross border terrorism, military action, and surrender. While West Pakistan viewed this war as a great betrayal by East Pakistan, a potent section of the Bengalis saw it as a war of liberation from an oppressive and brutal political system. Even the publication of the Hamood-ur-Rahman Commission Report in 2000 has not removed all the uncertainties. In most publications concerned with the 1971 war, the political and diplomatic aspects have been in the foreground while the military aspect has been neglected. This book redresses the balance. While the political aspects are given proper attention, the focus of the book is the military resistance of an isolated army. a necessary text for all interested in the course of Pakistan's history."-
Include Appendix
Keywords: India-Pakistan Conflict (1971) -- Qureshi, Hakeem Arshad -- Pakistan -- History, Military